Radical Islamism in the context of Arab Spring: shaping Rouhani’s Policies towards women in Iran - Teckchandani, Dr. Jyotika (IJRDO - Journal of Social Science and Humanities Research, 2017)
Hasan Rouhani won the election of 7th President of Islamic Republic of Iran in June 2013 on two significant promises: a nuclear deal with USA and relaxing of Islamic orthodoxy on women in Iran. Both issues are linked to each other in order to normalize relations with the West, particularly United States of America and attract the western investment that in turn would gradually lead to end of the isolation of Iran, an end to sanctions, spiraling inflation and scarcity and development of an improved economy. While significant progress has been made in the direction of nuclear deal as evident from several rounds of negotiation between Iran and P5+ 1 leading to Agreement on Framework, however not much significant steps have been undertaken to liberalize the issues related to civil and political liberty, human rights and women rights in particular. On the contrary conditions and rights related to these fields have further deteriorated. This paper concerns and intends to explain the reasons that obstruct the Rouhani government to unleash the reformist measures, notwithstanding having the intentions and desires to do so.